THE EXPERT VALIDATION OF GAME-BASED INTERACTIVE MULTIMEDIA IN THE DIGITALIZATION ERA FOR ELEMENTARY SCHOOL STUDENTS - Dwi Yuniasih Saputri; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to analyze the results of expert validation on game-based interactive multimedia development as an effort to improve the cognitive abilities of elementary school students. This study was development research involving the stages of a preliminary study, product development, and testing. Validation was one of the stages in a product development. It was carried out by material experts and media experts. The validation results were analyzed by converting quantitative data into qualitative data on a scale of five. The data of the development validation results were in the form of the validity percentage of the interactive multimedia to improve the cognitive abilities of elementary school students. The results of the interactive multimedia validation showed that the mean score of the validation from the media experts was 4.28 which was included in very good category, and the mean score of the validation from material experts was 4.27 which was included in very good category. Experts generally commented that gamebased interactive multimedia was good and interesting and it could be used in the learning activities. Then, the researcher made revisions according to the inputs received from the experts. Improvements in interactive multimedia included adding a button to return to the main menu and the exit button, changing the menu, simplifying the material so that it was not too dense, changing the font size in less readable parts, adding references, moving cartoon characters' feet and hands while walking, and changing evaluation questions.